Effects of molecular geometry on the efficiency of intramolecular charge transfer-based luminescence in o-carboranyl-substituted 1H-phenanthro[9, 10-d]imidazoles. Issue 3 (17th December 2021) - Im, Sehee; Ryu, Chan Hee; Kim, Mingi; You, Dong Kyun; Yi, Sanghee; Lee, Wonchul; Lee, Kang Mun
Abstract : The distinct difference in solid-state emission efficiency between 1 H -phenanthro[9, 10- d ]imidazole– o -carboranyl luminophores showed that the geometric orientation is a key factor for controlling intramolecular charge transfer-based radiative decay. Abstract : Herein, we compared the optical properties of four compounds with an o -carborane cage linked to 1 H -phenanthro[9, 10- d ]imidazole at the ortho - ( o PC ), meta - ( m PC ), or para -position ( p PC ) of the 2-phenyl ring or at the C2-position (PC ) of the phenanthroimidazole moiety. In the solid state, p PC and PC exhibited intense intramolecular charge transfer (ICT)-based emission centred at ∼560 nm, while o PC and m PC exhibited dual emission in high-energy ( λ em ≈ 385 nm) and low-energy ( λ em ≈ 580 nm) regions due to a locally excited transition and ICT-based emission, respectively. Thus, the quantum efficiency and radiative decay constant of ICT-based emission in the film state were much higher for p PC and PC than for o PC and m PC . Analysis of solid-state molecular structure revealed a notable geometric difference between these two pairs, showing that the C–C bond axis of the o -carborane was orthogonal to the plane of the appended aromatic group for p PC and PC but not for o PC and m PC . Theoretical modelling of the low-energy transition in the first excited states of p PC and PC upon the rotation of the o -carborane cage verified that the above orthogonality plays an important role in the maximisation of ICT-based luminescence. Our findings suggest that the molecular geometry around the o -carborane cage is a major factor determining the efficiency of ICT-based radiative decay in o -carboranyl-substituted π-conjugated fluorophores.